2014
DOI: 10.1016/j.jalz.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive concerns, episodic memory, and the APOE ε4 allele

Abstract: Background Subjective cognitive concerns may represent a simple method to assess likelihood of memory decline among APOE ε4 carriers. Methods We examined the relationship of self-reported subjective cognitive concerns, using 7 specific cognitive concerns, with memory and memory decline over 6 years among APOE ε4 carriers and non-carriers from the Nurses’ Health Study. Results In both groups, increasing subjective cognitive concern score predicted worse baseline memory and faster rates of subsequent memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 41 publications
6
50
1
Order By: Relevance
“…As shown in Table 1, the SCD- and SCD+ groups did not differ significantly from each other on any demographic variable, APOE ε4 allele status, or family history of dementia (all p > 0.10). The proportion of APOE ε4 allele carriers in the sample was 27%, which is similar to prevalence estimates that have been reported in other healthy adult samples [34]. As expected, no evidence of cognitive impairment was present in the sample at baseline; the average MMSE [21] score was 29.16 ± 0.94.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As shown in Table 1, the SCD- and SCD+ groups did not differ significantly from each other on any demographic variable, APOE ε4 allele status, or family history of dementia (all p > 0.10). The proportion of APOE ε4 allele carriers in the sample was 27%, which is similar to prevalence estimates that have been reported in other healthy adult samples [34]. As expected, no evidence of cognitive impairment was present in the sample at baseline; the average MMSE [21] score was 29.16 ± 0.94.…”
Section: Resultssupporting
confidence: 84%
“…Further, the SCD groups in our sample did not significantly differ based on family history of dementia or APOE ε4 status, which are two well-established risk factors for Alzheimer disease [27]. The proportion of APOE ε4 allele carriers in our sample was similar to the prevalence estimates found in other cognitively normal adult samples [34]. …”
Section: Discussionsupporting
confidence: 78%
“…Given that our sample is enriched with AD FH and APOE4 positive adults; and the observed association between these familial/genetic factors and increased SCC (Dik et al, 2001; Kryscio et al, 2014; La Rue et al, 1996; Risacher et al, 2015; Samieri et al, 2014; Small et al, 2001; Tsai, Green, Benke, Silliman, & Farrer, 2006), we investigated the association between SCC and FH and APOE4 status. Our analyses revealed that neither FH nor APOE4 status was associated with Visit 1 or longitudinal self- and informant-SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Of 68,590 nurses who returned the 2012 questionnaire, we excluded 4 participants aged .55 y in 1976, 49 participants with missing information on height, and 3130 participants who were diagnosed with any of 11 chronic diseases (e.g., cancer and myocardial infarction, as addressed below) before baseline. We also excluded 480 participants who skipped .5 items on the physical function scale and 12,792 participants who skipped any item on the subjective memory or 15-item Geriatric Depression Scale (GDS-15) score, as we previously documented (21,22), which left 52,135 participants available for the present analyses (Supplemental Figure 1). The participants aged 33.5-60.6 y in 1980 and 65.5-93.3 y in 2012.…”
Section: Study Populationmentioning
confidence: 99%
“…Subjective memory complaints have been associated with performance on objective cognitive tests (21,22). No more than 1 memory complaint was considered as the absence of impairment of memory.…”
Section: Assessment Of Memorymentioning
confidence: 99%